PENERAPAN JSA SEBAGAI UPAYA PENCEGAHAN KECELAKAAN KERJA DALAM KEGIATAN PERBAIKAN INTERNAL PART & BURNER TILE - SHERINA DWI LESTARI; ERRY YULIAN TRIBLAS ADESTA; ATIDIRA DWI HANANI (GANEC SWARA, 2024)
In this company, annual factory repair activities or Turn Around (TA) is a periodic maintenance program of factory facilities, where various work activities are carried out in a certain period of time, and involve so many people with various levels of expertise and work skills. This research was taken using a qualitative research method, namely by describing how the application of Job Safety Analysis (JSA) is carried out on internal part repair work and burner tile replacement in Turn Around (TA) activities in accordance with existing conditions, developing commitments and policies, or ongoing processes. The results of the reseacrh obtained based on in-depth observation and interviews found several potential hazards in this work, including the fall of the workpiece (18 work steps) 2 medium and 16 high, height (13 work steps) 3 medium and 10 high, dusty conditions (19 work steps) 3 medium and 16 high, gas poisoning (16 work steps) 1 medium and 15 high, hot conditions (17 work steps) 3 medium and 14 high, pinched (11 work steps) 2 medium and 9 high, and sparks (5 work steps) 1 medium and 4 high. The application of Job Safety Analysis in evaluating this job shows that comprehensive hazard identification, accurate risk analysis, implementation of effective preventive measures, and adequate training and supervision to ensure work safety